The Impact of Demographic Factors on Information Communication Technology Use: A Case of Mathematics Teachers in Kathmandu District - Adhikari, Ganesh Prasad (Academia Research Journal, 2024)
The use of information and communication technology (ICT) is an important issue for teaching learning activities due to global changes; however, the success of this use depends on the readiness of the teachers. This study investigated the effect of demographic variables on the use of ICT among secondary-level mathematics teachers in the Kathmandu district. This study describes a research hypothesis testing the absence of statistically significant differences in ICT use based on demographic variables such as gender, age, marital status, teaching experience, educational level, job position, and school location. For quantitative research, an online survey design was used. The data were collected through a validated online survey questionnaire, which consisted of seven demographic variables and seven items on the use of ICT. The online survey questionnaire was administered to 287 subjects. The response of mathematics teachers was only 59.23%. The response data was downloaded into Excel and cleaned. Frequency, percentage, independent sample t-tests, and one-way ANOVA were used to analyze the cleaned data using the JAMOVI software. The results revealed no statistically significant differences in ICT use across demographic variables. Specifically, gender, marital status, age groups, teaching experience, educational level, job positions, and school locations did not significantly affect the use of ICT among secondary-level mathematics teachers. The small effect sizes limited practical significance, despite the absence of statistical significance. The findings provide valuable insights into the relationship between demographic factors and ICT integration in education. Further research should validate these results in diverse educational contexts in Nepal.